The Characteristics of Synbiotic Yoghurt Ice Cream Made from Ice Cream Mix and Purple Yam Yoghurt (Dioscorea alata) - Rosida; Sarofa, Ulya; Wardhani, Raden Roro Regita Prasetyo (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2022)
Synbiotic yoghurt ice cream is a kind of ice cream made from ice cream mix (milk, skim milk and sugar) and purple yam yoghurt as the main ingredient. The inulin, prebiotic compound of purple yam, inulin, can trigger the growth of beneficial bacteria so it would beneficial for the health. The addition of stabilizer, xanthan gum, aims to produce yoghurt ice cream with a soft texture. The aim of this study to determine the effect of proportion of ice cream mix:yoghurt and concentration of xanthan gum on yoghurt ice cream characteristics. This study used a completely randomized design-factorial pattern with two factors and three replications. The factors are proportion of ice cream mix:yoghurt (70:30; 60:40; 50:50) and concentration of xanthan gum (0.1%; 0.2%; 0.3.%). The observed data were analyzed using ANOVA, followed by DMRT test at 5% level if there were significant differences. The study revealed that the best treatment, based on physicochemical properties of ice cream, is the proportion of ice cream mix:yoghurt (60:40) and xanthan gum concentration (0.2%) with total LAB of 8.55 log CFU/ml; overrun 27.69%; melting time 13.51 min/10 gr; total dissolved solids 31.00 OBrix; viscosity 517.00 mPas. Keywords: yoghurt ice cream, synbiotic, purple water yam, xanthan gum